Japanese women and sport : beyond baseball and sumo - Kietlinski, Robin (Globalizing sport studies., 2011)
In 'Japanese Women and Sport', Robin Kietlinski sets out to problematize the hegemonic image of the delicate Japanese woman, highlighting an overlooked area in the history of modern Japan. Previous studies of gender in the Japanese context do not explore the history of female participation in sport, and recent academic studies of women and sport tend to focus on Western countries. Kietlinski locates the discussion of Japanese women in sport within a larger East Asian context and considers the socio-economic position and history of modern Japan. Reaching from the early 20th century to the prese.